2018
DOI: 10.1002/14651858.cd009860.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for trigger finger

Abstract: Analysis 9.1. Comparison 9 Open surgery by transverse incision of the skin in the distal palmar crease versus open surgery by transverse incision of the skin about 2-3 mm distally from distal palmar crease, Outcome 1 DASH score. .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
0
13

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(89 citation statements)
references
References 66 publications
2
74
0
13
Order By: Relevance
“…In the event of full reduction of symptoms and then recurrence, a second injection may be used. There is less literature to confirm the efficacy of this and the literature that exists shows decreased rates of success [70,71,76]. DASH scores may be useful in determining the likelihood of failure following injection [71].…”
Section: Injection Techniquesmentioning
confidence: 98%
See 3 more Smart Citations
“…In the event of full reduction of symptoms and then recurrence, a second injection may be used. There is less literature to confirm the efficacy of this and the literature that exists shows decreased rates of success [70,71,76]. DASH scores may be useful in determining the likelihood of failure following injection [71].…”
Section: Injection Techniquesmentioning
confidence: 98%
“…Symptom reduction of stenosing tenosynovitis is similar between surgery and corticosteroid injections. While surgical intervention had lower recurrence of symptoms long term, it is associated with longer-lasting pain after the intervention [70]. Disability of arm shoulder and hand (DASH) score may be useful in determining which patients may benefit from surgery [71].…”
Section: Stenosing Tenosynovitismentioning
confidence: 99%
See 2 more Smart Citations
“…Fiorini et al 30 conducted a systematic review of trigger finger treatment and concluded that open surgery has a lower recurrence rate when compared with patients treated with infiltration. Brozovich et al 3 pointed out that from a purely financial point of view, women without diabetes with trigger thumb should receive up to two infiltrations before being submitted to percutaneous release.…”
Section: Final Considerationsmentioning
confidence: 99%